High Viral Load and Respiratory Failure in Adults Hospitalized for Respiratory Syncytial Virus Infections. (22nd April 2015) - Lee, Nelson; Chan, Martin C. W.; Lui, Grace C. Y.; Li, Ran; Wong, Rity Y. K.; Yung, Irene M. H.; Cheung, Catherine S. K.; Chan, Eugenia C. Y.; Hui, David S. C.; Chan, Paul K. S.
Abstract: A prospective study among adults hospitalized for polymerase chain reaction–confirmed respiratory syncytial virus infections (n = 123) showed frequent occurrence of lower respiratory-tract complications causing respiratory insufficiency (52.8%), requirement for assisted ventilation (16.3%), and intensive care unit admission/death (12.2%). High viral RNA concentration was detected at time of hospitalization, including in patients who presented later than 2 days of illness (day 1–2, 7.29 ± 1.47; day 3–4, 7.28 ± 1.41; day 5–8, 6.66 ± 1.87 log10 copies/mL). RNA concentration was independently associated with risk of complications and respiratory insufficiency (adjusted odds ratio 1.40 per log10 copies/mL increase, 95% confidence interval, 1.03–1.90; P = .034). Our data indicate the need and provide a basis for clinical research on antiviral therapy in this population.